Opera of martha or the fair at richmond - FLOTOW, F. Von (Oliver Ditson)
OverturenNo. 1 Ladies chorus tu piu vaga duna stella....nNo. 2. Duet questo duol che si v'affannonNo. 3. Terzetto ah! che matto, che figuranetc.